Periprocedural Antibiotic Prophylaxis Practice during Diagnostic Cystoscopy: An Observational Study - Phuyal, Anjit; Chapagain, Suman; Chalise, Pawan Raj; Luitel, Bhojraj; Poudyal, Sujeet; Gyawali, Prem Raj (Journal of Institute of Medicine Nepal, 2024)
Introduction Both American and European guidelines recommend against routine use of antibiotics prophylaxis in routine cystoscopy. But studies have shown that antibiotics use during cystoscopy is discordant from available guideline recommendations even in Europe and America. This study aims to identify prophylactic antibiotic uses pattern of Nepalese Urologists and measure adherence to guidelines. Methods An online questionnaire based self-reported survey was conducted among the practicing urologists of Nepal, who were full members of Nepalese Association of Urologists. The questionnaires in Google Forms were sent via emails to 96 urologists of Nepal. Fully completed questionnaires were analyzed. Results Out of 96 emails 58 fully filled questionnaires were received and analyzed. Routine prophylactic antibiotics prescription before cystoscopy was reported by 43 (74.1%) urologists. Availability of Antibiotic Stewardship/Antimicrobial Stewardship team at their workplace was reported by 31 (53.4%) urologists and 19 (32.8%) urologists reported of having Standard Operating Procedure regarding peri-procedural antibiotic prophylaxis at their workplace. No verification of the answers were done and reported as received. Conclusion Peri-procedural antibiotic prophylaxis practice during cystoscopy was highly prevalent.